KOSAKATA BUDAYA TRADISI PENANGKAPAN KOTEKLEMA DI LAMALERA DALAM NOVEL “SUARA SAMUDRA, CATATAN DARI LAMALERA” SEBAGAI SALAH SATU ALTERNATIF PENGAYAAN KOSAKATA BAHASA INDONESIA - Nining Nur Alaini (MABASAN, 2018)
The three local languages mentioned in the National Language Policy formulated in the Language Politics seminar organized by the Language Center (now the Agency for Language Development and Development) in 1999 function as a language symbols including a symbol of regional identity, and a symbol of regional pride; a mean of communication in the family and local communities, and a mean of supporting regional culture and as a supporter of regional literature and Indonesian literature. As a means of supporting the Indonesian language, regional languages have a dominant role in enriching the Indonesian vocabulary. This paper will describe the cultural vocabulary in the tradition of capturing the koteklema in Lamalera in the novel of "Suara Samudra, Catatan dari Lamalera", as one of the alternative of Indonesian vocabulary enrichment. The novel of "Suara Samudra, Catatan dari Lamalera", by Maria Matildis Banda, reveals a cliché theme often appears and is raised in Indonesian novels about the relationship of two lovers due to social status differences. The novel is interesting as it is written in a traditional village setting, tradition and culture of fishing and whaling in Lamalera. This novel is an ethnographic novel that presents the traditions and culture of Lamalera through the physical and cultural background of fishermen in Lamalera. Maria Matildis Banda conveys local color through literature. His language, diction, and power of speaking in a local dialect enrich the literary treasures of Indonesia. This condition is one of the reasons for the importance of 'adopting' the registers in the novel into the Indonesian vocabulary, so that Indonesian language can further develop itself in order to play a maximum role as a means of communication in various domains of the usage, as well as play an increasingly steady role as a language amplifier for an identity and character of the nation.